An ecological study of reintroduced Arabian oryx in the 'Uruq Bani Ma'arid protected area of the Kingdom of Saudi Arabia - Bothma, Jacobus du P. (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2006.